6,8-Dibromo-4-oxo-4H-chromene-3-carbaldehyde - Yoshinobu Ishikawa (Acta crystallographica. Section E, Structure reports online, 2014)
In the title compound, C10H4Br2O3, the atoms of the 6,8-dibromochromone unit are essentially coplanar [largest deviation from the mean planes = 0.1109 (3) Å] and the formyl group is twisted slightly with respect to the attached ring [C—C—C—O torsion angles = 11.5 (4) and −168.9 (3)°]. In the crystal, molecules are linked to each other through halogen bonds [Br...O = 3.118 (2) Å, C—Br...O = 162.37 (8) and C=O...Br = 140.20 (15)°]. The molecules are further assembled via π–π stacking interactions [centroid–centroid distance = 3.850 (2) Å].